The effect of “invisible” tax preferences on investment and tax preference measures - Robinson, Leslie A.; Sansing, Richard (Journal of Accounting and Economics, 2008)
This paper develops and analyzes a model in which tax considerations and financial reporting considerations have countervailing effects on a firm's investments in internally developed intangible assets. It also proposes and estimates a new measure of tax preferences, which we call the economic effective tax rate. This measure reflects both investments in intangible assets and the use of debt financing, neither of which generates a book-tax difference. Our measure indicates that the economic effective tax rate was about 18 percent between 1988 and 2005, when the statutory tax rate was either 34 or 35 percent.